Atmospheric pollution of the Ural Federal District subjects (2016): regional features - Petrov, A I; Petrova, D A (IOP conference series. Earth and environmental science, 2018)
The article deals with regional characteristics of the atmosphere ecology in the Ural Federal District (UFD). The official Rosstat data is given on total emissions of pollutants into the atmosphere of the Urals. Analytical work was carried out to assess the specific (for 1 person/year and for 1 km2/year) total air emissions of pollutants and their distribution by sources of pollution - stationary and mobile. On the basis of data analytics, conclusions are drawn about regional peculiarities of atmospheric pollution in UFD subjects. It is established that atmospheric pollution in the UFD in terms of specific (for 1 person/year and for 1 km2/year) indicators significantly exceeds the all-Russian level by almost 2 times. In the subjects of the Ural Federal District, a significant spatial uneven distribution of air pollution is formed. The fact of neglecting the necessity of trapping and neutralizing pollutants is revealed in the Khanty-Mansiysk Autonomous District (Yugra) and the Yamalo-Nenets Autonomous District.